University students’ knowledge and attitudes towards leprosy - Graciano-Machuca, Omar; Velarde-de la Cruz, Erandi Enif; Ramirez-Dueñas, Maria Guadalupe; Alvarado-Navarro, Anabell (The Journal of Infection in Developing Countries, 2013)
Introduction: Patients with leprosy may be affected psychologically and socially by the negative attitude of society toward leprosy, caused by widespread ignorance and prevailing stereotypes surrounding the disease. This study aimed to determine the knowledge and attitudes toward leprosy among students at the University of Guadalajara. Methodology: This descriptive cross-sectional study included 1,300 students over 18 years of age from various Thematic University Centres in Guadalajara. Students’ degree subjects included the health sciences, humanities, exact sciences (i.e., chemistry, physics), arts, biological-agricultural sciences, and administration. Students were randomly selected regardless of gender and all students were enrolled in either the first, second, or third year of their undergraduate studies. Results: Overall, students showed an intermediate level of knowledge of leprosy. Results showed that 67% correctly responded that leprosy is an infectious disease, 64% knew of the presence of skin lesions, and 60% knew that a microbe causes the disease. Furthermore, 45% correctly responded that leprosy is a disease associated with poverty and 40% responded that leprosy is disabling. Only 31% stated that leprosy is curable. Negative attitudes were evident regarding the question of employing a leprosy patient (57%) and having a leprosy patient as a spouse or partner (30%). Discussion: The results revealed that there is insufficient knowledge of and poor attitudes toward leprosy among students at the University of Guadalajara. It is necessary to improve current health education measures by using updated educational strategies to reduce the stigma of leprosy and the segregation of leprosy patients and their families.